2014
DOI: 10.1182/blood-2013-12-546218
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin relieves lentiviral vector transduction resistance in human and mouse hematopoietic stem cells

Abstract: Key Points Rapamycin significantly enhances lentiviral vector gene delivery to hematopoietic stem cells while preserving engraftment potential. Rapamycin-mediated transduction enhancement is not accompanied by alterations in lentiviral integration profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 57 publications
4
75
0
1
Order By: Relevance
“…However, the addition of rapamycin during VSV-G-LV transduction of resting hCD34 1 cells did not significantly increase transduction. 61,62 This is in accordance with the absence of the VSV receptor low-density lipoprotein on resting hCD34…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, the addition of rapamycin during VSV-G-LV transduction of resting hCD34 1 cells did not significantly increase transduction. 61,62 This is in accordance with the absence of the VSV receptor low-density lipoprotein on resting hCD34…”
Section: Discussionsupporting
confidence: 81%
“…However, caution is warranted because of the known cell cycle blockage this drug induces. 61 We identified CD46 as the MV receptor that allows this spectacular H/F-LV transduction efficiency for as well as quiescent as cytokine-stimulated HSCs. This is reinforced by the fact that retronectin increased H/F-LV transduction of resting CD34…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Most of these methods, however, result in only incremental effects on overall transduction efficiency, are not scalable (centrifugation), are highly dependent on vector quality (infectious titer), and are subject to patient-specific variability. Recently, however, Wang and Torbett [14] reported that rapamycin enhanced lentiviral transduction of cord blood and bone marrowderived HSPCs from several species. Rapamycin (sirolimus) is a nonantibiotic macrolide with pleiotropic activity, including immunosuppression and regulation of cell cycling and autophagy [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%